CONSEQUENCES OF COGNITIVE CHANGES IN THE BRAIN OF ELDERLY PEOPLE WITH INSOMNIA - Gulasalxon Qosimova Yuldashali qizi (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article explores the intricate relationship between insomnia and cognitive changes in elderly individuals. It delves into the potential consequences of chronic sleep disturbances on brain health, including cognitive impairment and neurodegeneration. Through a comprehensive review of existing literature, we examine the methods used to study this phenomenon, present key findings, and discuss implications for clinical practice and future research.